2016
DOI: 10.1099/mgen.0.000090
|View full text |Cite
|
Sign up to set email alerts
|

Putatively novel serotypes and the potential for reduced vaccine effectiveness: capsular locus diversity revealed among 5405 pneumococcal genomes

Abstract: The pneumococcus is a leading global pathogen and a key virulence factor possessed by the majority of pneumococci is an antigenic polysaccharide capsule (‘serotype’), which is encoded by the capsular (cps) locus. Approximately 100 different serotypes are known, but the extent of sequence diversity within the cps loci of individual serotypes is not well understood. Investigating serotype-specific sequence variation is crucial to the design of sequence-based serotyping methodology, understanding pneumococcal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 44 publications
4
62
0
Order By: Relevance
“…We further unveiled the mosaic nature of pneumococcal histidine triad proteins, and especially vaccine candidate PhtD, variation of which is facilitated both by the aforementioned chromosomal inversion and more local recombination events. This observation expands the set of previously identified highly variable pneumococcal antigens (76,77). Figure 5).…”
Section: Discussionsupporting
confidence: 84%
“…We further unveiled the mosaic nature of pneumococcal histidine triad proteins, and especially vaccine candidate PhtD, variation of which is facilitated both by the aforementioned chromosomal inversion and more local recombination events. This observation expands the set of previously identified highly variable pneumococcal antigens (76,77). Figure 5).…”
Section: Discussionsupporting
confidence: 84%
“…For example, the csu region has been altered multiple independent times in A. baumannii (13, 15) and we observed both increased and decreased expression relative to that in isogenic isolates from several patients. In an analysis of IS locations in over 1,000 A. baumannii genomes, the 5-kbp region containing the csu genes had over 90 independent insertion events, a density approximately three times higher than that in any other 5-kb region of the genome (12). This provides compelling evidence that alteration of this region is under selection.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, genomic reads were mapped to the first isolate from the series and SNVs were called with FreeBayes (arXiv:1207.3907v2). Insertion sequence events were identified with ISseeker (12). Clade level genetic differences were identified by assembly-based SNV calling in kSNP (51) and verified manually to confirm that variants were isolate, patient, or clade specific by using blast queries with all of the available A. baumannii genomes in the UHHS population (11, 13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising as the pneumococcus is known to undergo frequent recombination (Feil et al, 2000;Henriques-Normark et al, 2008;Vos and Didelot, 2009), and the capsular locus was shown to be a recombination hotspot (Croucher et al, 2011;Chewapreecha et al, 2014). Furthermore, we know from previous studies that the extent of within-serotype diversity is under-appreciated, with many hybrid serotypes circulating in the population (Salter et al, 2012;van Tonder et al, 2016). However, the evolutionary dynamics, and hence the full adaptive potential of pneumococcal capsular polysaccharides, are not well understood.…”
Section: Introductionmentioning
confidence: 99%